Zelik Oksana. The literary views of Mykhailo Mohyliansky and Kyiv neoclassical writers: a comparable aspect - Zelik Oksana (Philological Treatises, 2020)
The article deals with a comparative analysis of literary views of Mykhailo Mohyliansky and Kyiv neoclassical writers. There are compared aesthetic and cultural aspects. The main directions of literary and literary-critical activities of scientists, the range of research interests are analyzed. Also creative and friendly relations of scientists are observed. The scientific view focuses on the search for methodological research, the use of literary theories. The analysis demonstrates common scientific paradigm of neoclassical writers and Mykhailo Mohyliansky.